2018
DOI: 10.4236/ce.2018.916201
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Readiness to Learn: Benefits of Executive Function Training in Kindergarten Carry over to First Grade

Abstract: Executive Function skills such as focused attention, inhibition or self-control, and working memory in preschool and kindergarten predict reading and math achievement in elementary school and beyond. A growing body of research indicates that these skills can be improved by repetitive practice of progressively more difficult tasks that require Executive Function. We report that children who participated in an integrated program of computer presented and physical exercises to improve Executive Function when in k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(32 reference statements)
0
1
0
Order By: Relevance
“… Imal and Wexler (2018) demonstrated that executive function training is beneficial to learning and increasing “school readiness.” The researchers found weekly brain training implemented across a 4-month period in kindergarteners significantly increased student gains on school-administered achievement tests in first grade. These findings illustrate the relationship between cognitive skill development and the far-transfer of skills that foster academic achievement ( Wexler et al, 2016 ; Imal and Wexler, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“… Imal and Wexler (2018) demonstrated that executive function training is beneficial to learning and increasing “school readiness.” The researchers found weekly brain training implemented across a 4-month period in kindergarteners significantly increased student gains on school-administered achievement tests in first grade. These findings illustrate the relationship between cognitive skill development and the far-transfer of skills that foster academic achievement ( Wexler et al, 2016 ; Imal and Wexler, 2018 ).…”
Section: Introductionmentioning
confidence: 99%